Avaliação do potencial terapêutico da Valeriana officinalis e do disseleneto de difenila frente à toxicidade induzida por rotenona em Drosophila melanogaster - Sudati, Jessie Haigert (2012)
Among various antioxidant therapeutic applications, neuroprotective action is highlighted sinceoxidative stress is recognized as one of the events involved in cell damage which occur in most of neurological disorders, including Parkinson s disease (PD). Consequently, the search for natural and/or synthetic antioxidants which may be effective in the treatment of neurological disorders has grown over the past years. In this context, several studies have shown the antioxidant potential of selenium organic compound diphenyl diselenide (DPDS) in vitro and in vivo, but there are still few studies talking about antioxidant activity of Valeriana officinalis (V. officinalis). Likewise, there is no research on the possible beneficial effects of these agents in models of neurological diseases such as PD using Drosophila melanogaster (D. melanogaster), an specie that has been used with great reliability in the reproduction of dopaminergic dysfunction models. Thus, the objective of this study was to evaluate the in vitro antioxidant activity of V. officinalis, as well as, the effect of supplementation of extract from roots of this plant and DPDS on behavioral and biochemical changes induced by pesticide rotenone exposure in D. melanogaster. As a result, we verify that: ethanolic extract from V. officinalis inhibited the generation of TBARS caused by various pro-oxidants agents in rat s brain homogenate in vitro, diminished deoxyribose degradation and generation of reactive oxygen species (ROS) caused by quinolinic acid (QA); flies exposed to rotenone were significantly lower than control group in behavioral tests of climbind and open-field (number of crossings and immobility time) and higher incidence of mortality. V. officinalis treatment was effective in reducing these effects, except against the decrease in number of crossings. Exposure to rotenone decreased in flies cell viability and non protein thiol content, but V. officinalis treatment normalized to the control levels. Rotenone increased mRNA expression on superoxide dismutase (SOD), catalase (CAT) and tyrosine hydroxilase (TH) enzymes, which were restored by treatment with V. officinalis; DPDS supplementation was not effective in offering protection against locomotor and biochemical alterations induced by rotenone. In addition, DPDS per se induced an increase in ROS production and decreased survival rate of flies. In general, data showed that V. officinalis may be a promising neuroprotective agent, since it was effective in reducing the oxidative damage caused by different neurotoxic agents and toxic effects caused by rotenone exposure. Thus, the use of this plant extract may be beneficial in reducing neurological disorders associated to the oxidative stress. In relation to the use of DPDS, further studies aimed at the concentrations used are necessary, given that the concentration tested in this work did not offer protection against rotenone damage effects, DPDS potentiated the effect of this pesticide on mortality and exhibited toxic effects per se. Overall, these results contribute to the advancement of research focused on the toxicology and pharmacology of natural and synthetic products and screening for agent that provide neuroprotection and may be promising to assist in the treatment of neurodegenerative diseases, including PD.